2020
DOI: 10.1007/s00705-020-04704-5
|View full text |Cite|
|
Sign up to set email alerts
|

Transmission studies of the newly described apple chlorotic fruit spot viroid using a combined RT-qPCR and droplet digital PCR approach

Abstract: The transmission of the apscaviroid tentatively named apple chlorotic fruit spot viroid (ACFSVd) was investigated using a one-step reverse-transcription (RT) droplet digital PCR assay for absolute quantification of the viroid, followed by quantification of relative standard curves by RT-qPCR. Our results indicate that ACFSVd is effectively transmitted by grafting, budding and seeds. No transmission has yet been observed to the viroid-inoculated pome fruit species Pyrus sp. and Cydonia sp. ACFSVd was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…ASSVd is seed-borne in apple [ 46 ], and seedlings germinated from ASSVd-positive apple seeds demonstrated a 7.7% infection rate [ 29 ]. ACFSVd is seed-transmitted from symptomatic apple fruit; seedlings that germinated from infected apple seeds showed an infection rate of 2.8% [ 10 ]. Transmission of GYSVd-1 via infected seeds in eight grapevine varieties has been demonstrated [ 56 , 57 ].…”
Section: Seed and Pollen Transmissionmentioning
confidence: 99%
See 3 more Smart Citations
“…ASSVd is seed-borne in apple [ 46 ], and seedlings germinated from ASSVd-positive apple seeds demonstrated a 7.7% infection rate [ 29 ]. ACFSVd is seed-transmitted from symptomatic apple fruit; seedlings that germinated from infected apple seeds showed an infection rate of 2.8% [ 10 ]. Transmission of GYSVd-1 via infected seeds in eight grapevine varieties has been demonstrated [ 56 , 57 ].…”
Section: Seed and Pollen Transmissionmentioning
confidence: 99%
“…ACFSVd was transmitted by two species of aphids and by the larvae of a codling moth that had been feeding directly on symptomatic, viroid-infected apple trees [ 10 ]. Desvignes [ 72 ] reported that Myzus persicae (the green peach aphid) experimentally transmitted PLMVd, but at a low rate, suggesting minor relevance under natural peach-orchard conditions [ 82 ].…”
Section: Vector Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this means that dPCR is even suitable for the preparation of in-house reference materials, which is particularly important in the field of plant pathogen diagnostics, where no reference materials are commercially available. Reverse-transcription (RT) digital PCR has been applied for the absolute quantification of viruses and viroids [60,64], with the aim of identifying the main transmission routes, main transmission vectors, and the plants carrying latent infections-a step of great relevance in the control and certification of nurseries' plants.…”
Section: Phytopathogens Diagnosticsmentioning
confidence: 99%